2019
DOI: 10.1051/e3sconf/201910000066
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance in airborne bacteria isolated from waste management and wastewater treatment plants in Olsztyn

Abstract: Wastewater treatment plants (WWTPs) and municipal waste management plants (MWMPs) emit bioaerosols containing potentially pathogenic biological components which post a threat for human health. Microbiological monitoring supports evaluations of the antibiotic resistance (AR) of airborne microorganisms and the relevant health risks. The aim of this study was to analyze the microbiological quality of air sampled in a WWTP and MWMP in Olsztyn based on total bacterial counts, the presence of bacteria resistant to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The copy numbers of ARGs and the 16S rRNA gene were considerably higher than those reported by Gao et al [23] in a composting plant even though both the analyzed WMP and the cited composting plant processed waste in biological reactors where significant amounts of heat are generated. In a previous study conducted in the same WMP, a similar group of predominant ARGs was identified in the air in MP and BP units [14]. The observed increase in the copy numbers of tet(A), tet(B), tet(M), bla AMP-C , bla TEM , floR genes, and the 16S rRNA gene in spring could be attributed to a higher volume of managed waste.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The copy numbers of ARGs and the 16S rRNA gene were considerably higher than those reported by Gao et al [23] in a composting plant even though both the analyzed WMP and the cited composting plant processed waste in biological reactors where significant amounts of heat are generated. In a previous study conducted in the same WMP, a similar group of predominant ARGs was identified in the air in MP and BP units [14]. The observed increase in the copy numbers of tet(A), tet(B), tet(M), bla AMP-C , bla TEM , floR genes, and the 16S rRNA gene in spring could be attributed to a higher volume of managed waste.…”
Section: Discussionsupporting
confidence: 67%
“…In a preliminary analysis, the presence of four tetracycline resistance genes (tet(A), tet(B), tet(M), tet(X)), 10 beta--lactam resistance genes (bla TEM , bla SHV , bla OXA , bla CTX-M , bla CTX-M-1 , bla CTX-2 , bla CTX-M-9 , bla VEB , bla CMY , bla AMP-C ), four chloramphenicol resistance genes (floR, cmlA, fexA, fexB) and the 16S rRNA gene was determined by PCR. All primers had been previously validated for primer sequences, amplicon sizes, and annealing temperatures (the references for each sequence and detailed information on PCR conditions are presented in previous studies by Osińska et al [13] and Potorski et al [14]).…”
Section: Methodsmentioning
confidence: 99%
“…The microbiological quality of air from a WRRF and municipal waste management (MWMP) based on total bacterial counts, presence of antibiotic-resistant bacteria, and genes-encoding resistance was assessed (Potorski, Koniuszewska, Czatzkowska, & Harnisz, 2019). In general, bacterial counts were higher in air samples from the MWMP (~10 4 CFU/m 3 ) compared to the WRRF (10-10 3 CFU/m 3 ) and the antibiotic resistance genes were most diverse in the biological area of the WRRF and in the mechanical segment of the MWMP.…”
Section: Odor Impacts/risk Assessmentsmentioning
confidence: 99%